Controlling the surface‐mediated release of DNA using 'mixed multilayers'. Issue 2 (26th August 2016) - Appadoo, Visham; Carter, Matthew C. D.; Lynn, David M.
Abstract: We report the design of erodible 'mixed multilayer' coatings fabricated using plasmid DNA and combinations of both hydrolytically degradable and charge‐shifting cationic polymer building blocks. Films fabricated layer‐by‐layer using combinations of a model poly(β‐amino ester) (polymer1 ) and a model charge‐shifting polymer (polymer2 ) exhibited DNA release profiles that were substantially different than those assembled using DNA and either polymer1 or polymer2 alone. In addition, the order in which layers of these two cationic polymers were deposited during assembly had a profound impact on DNA release profiles when these materials were incubated in physiological buffer. Mixed multilayers ∼225 nm thick fabricated by depositing layers of polymer1 /DNA onto films composed of polymer2 /DNA released DNA into solution over ∼60 days, with multi‐phase release profiles intermediate to and exhibiting some general features of polymer1 /DNA or polymer2 /DNA films (e.g., a period of rapid release, followed by a more extended phase). In sharp contrast, 'inverted' mixed multilayers fabricated by depositing layers of polymer2 /DNA onto films composed of polymer1 /DNA exhibited release profiles that were almost completely linear over ∼60‐80 days. These and other results are consistent with substantial interdiffusion and commingling (or mixing) among the individual components of these compound materials. Our results reveal this mixing to lead to new, unanticipated, and useful release profiles and provide guidance for the design of polymer‐based coatings for the local, surface‐mediated delivery of DNA from the surfaces of topologically complex interventional devices, such as intravascular stents, with predictable long‐term release profiles. Abstract : We report the fabrication and characterization of erodible, polymer‐based 'mixed multilayer' coatings fabricated using plasmid DNA and combinations of hydrolytically degradable and 'charge‐shifting' cationic polymer building blocks. Our results reveal this approach to lead to new, unanticipated, and useful DNA release profiles, and provide guidance for the design of thin, polymer‐based coatings for the local, surface‐mediated delivery of DNA from the surfaces of topologically complex objects and interventional devices, such as intravascular stents, with predictable and long‐term extended release profiles.